Issues for collaborative development of learning objects to support e-learning / M. Khalad Hasan, M. Shahidur Rahman and M. Zafar Iqbal - Hasan, M. Khalad; Rahman, M. Shahidur; Iqbal, M. Zafar (Penerbit UiTM (UiTM Press), 2008)
Learning objects are interactive visualizations of program code which focus on a specific learning goal and have the competence to improve the current E-learning environment radically. By reducing the complexity in learning computer programming these e-modules help the learners to better understand and master, and the teachers to better explain and illustrate the problems connected to the use of basic and advanced structures in computer programming. On the other hand, collaboration is the keyword that summarizes recent trends in information technology, especially in the world of academe. When content is developed in a collaborative environment, its scope and sustainability are simply increased.